Slowing Down - Moore, Nathan (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
Guitarist Nathan Moore relates his experiences as an improvising musician responding to COVID. In this piece, he describes the practice of recording solo improvisations that are then sent to colleagues for an overdubbed, improvised response.